Commemorare vittime di violenza: la street art come luogo di resistenza e discorso di positività - Lanslots, Inge; Sambre, Paul; Maestri, Eliana (Incontri. Rivista europea di studi italiani, 2020)
The commemoration of victims of violence Street art, activists and their messages of positivity The present article analyses how street art and activism intertwine in public spaces addressing wider audiences with messages of growing positivity. Via the comparative analysis of two case studies revolving around the ‘no mafia’ sign on the outskirts of Palermo (Capaci) and the mural dedicated to Carlo Giuliani at the entrance of the Garbatella area within the Ostiense quarter in Rome, we explore the genesis of both works, their specific spatial setting and the role of social actors in the conservation of the mural paintings, as well as in the commemoration of victims of violence. Our analysis draws on key theoretical findings conceptualized within memory studies, sociology and research on visual culture.